Regulation of G protein signaling by the 70 kDa heat shock protein - William K., Lim; Kimon C., Kanelakis; Richard R., Neubig (Elsevier B.V., 2013)
G protein-coupled receptors (GPCRs) transduce extracellular signals to the interior of the cell by activating membrane-bound guanine nucleotide-binding regulatory proteins (G proteins). An increasing number of proteins have been reported to bind to and regulate GPCRs. We report a novel regulation of the alpha2A adrenergic receptor (α2A-R) by the ubiquitous stress-inducible 70 kDa heat shock protein, hsp70. Hsp70, but not hsp90, attenuated G protein-dependent high affinity agonist binding to the α2A-R in Sf9 membranes. Antagonist binding was unchanged, suggesting that hsp70 uncouples G proteins from the receptor. As hsp70 did not bind G proteins but complexed with the α2A-R in intact cells, a direct interaction with the receptor seems likely. In the presence of hsp70, α2A-R-catalyzed [35S]GTPγS binding was reduced by approximately 70%. In contrast, approximately 50-fold higher concentrations of hsp70 were required to reduce agonist binding to the stress-inducible 5-hydroxytryptamine1A receptor (5-HT1A-R). In heat-stressed CHO cells, the α2A-R was significantly uncoupled from G proteins, coincident with an increased localization of hsp70 at the membrane. The contrasting effect of hsp70 on the α2A-R compared to the 5-HT1A-R suggests that during stress, upregulation of hsp70 may attenuate signaling from specific GPCRs as part of the stress response to foster survival.